THE BASIC ELEMENTS OF PAGUYUBAN NGESTI TUNGGAL - Dunkring, Ahmad Solahuddin (KALAM, 2018)
As an independent mysticism community which has an independent system belief and form of praying, etc., Paguyuban Ngesti Tunggal (Pangestu) does not force the members to come out of the religion they embraced. Pangestu explicitly declares as a community of mysticism that offering an oasis of spirituality, which is not given by a great religion, such as Islam, Christianity, Catholicism, etc. Thus, the Pangestu members have a dualistic belief at the same time: believing in their religion and believing in Pangestu. This paradox would be interesting to be a problem of research. In this case, I would like to examine Pangestu with the point of Durkheim theory that is the 'basic element' in rural religion. The point of view of the writer would be: system belief, practice relative and sacred thing. In the end, the conclusions of this study are: 1. The system belief of Pangestu including to: the concept of divinity in the form of Tripurusa; The ritual of worship is nyawiji (emanation) process between man and God; Rules of procedure, including to the orders in the form of Hastasila and prohibited in the form of Paliwara. 2. The practice relatife of Pangestu including to Bawa Raos that it to convey the core of Pangestu teaching and ceremonies held at every August 16th to commemorate the death of the holy man Pak Dhe Narto. 3. The Sacred thing of Pangestu which including to the grave, the house of Pak Dhe Narto which made as museum, the inscription, the flag, akik (the agate stone) that being spread over around the grave, etc. which it would be functioned as a reminder to the teaching of Guru Sejati.